The Influence of Utilisation the Contextual-Learning Materials in Discovery Learning Models on Physics Learning Outcomes - Suci Alvina Rahma; Eka Susanti; El Basthoh; Lelfita Lelfita (Physics Learning and Education, 2023)
This research was motivated by the low of students learning outcomes in grade X at SMAN 1 Enam Lingkung that students think physics is difficult. Based on this problem, the aim of this research is to determine the effect of using contextual-based learning materials in the discovery learning model on the physics learning outcomes of student in grade X at SMAN 1 Enam Lingkung. This is experimental quantitative research with population of 180 students with 68 students was chosen as the sample 68 by using purposive random sampling technique. Analysis of the similarity of means was used to test the hypothesis because the data is normally distributed and has a homogeneous variance. The results of the cognitive domain analysis obtained that the average of the experimental class was 72.12 and the control class was 62.29. It can be concluded that the class that use contextual-based learning materials shows higher average learning outcomes compared to that of the class without contextual-based learning materials. Analysis of mean similarity test was obtained th = 2.05 while tt = 1.998 at the 0.05 level of significance and dk = 66. It can be seen that th is in the Ho rejection area, this means that Ho is rejected and H1 was accepted. Based on this result it can be concluded that there is a significant influence of the use of contextual-based learning materials with discovery learning model on physics learning outcomes of student in grade X in SMAN 1 Enam Lingkung.